CaCO3 from Anadara granosa shell as reparative dentin inducer in odontoblast pulp cells: In-vivo study - Widya Saraswati; Adioro Soetojo; Nina Dhaniar; Hermawan Adi Praja; Ratih Mahanani Santoso; Nadiah Salsabila Nosla; Ganiezha Cindananti; Rossabella Vennowusky Rafli; Nabiela Rahardia (Journal of Oral Biology and Craniofacial Research)
Introduction: Anadara granosa (blood clam) shell contained 98.7% of calcium carbonate (CaCO3). This material has bio-properties that able to induced the dentin regeneration. This study is expected to reveal the nuclear factor kappa beta (NF-kB), transforming growth factor beta (TGF-β1), and vascular endothelial growth factor A (VEGF-A) expression in dental pulp after application of CaCO3 from Anadara granosa shell Material and methods: The thirty Rattus norvegicus strain Wistar used as model. The maxillary first molar was preparation using 0.84 mm low-speed diamond bur to made cavity. The cavity then applied glass ionomer cement (as control group) and other group applied CaCO3 from Anadara granosa shell. The teeth in each group were extracted after 1st, 3rd and 7th days of application for immunohistochemistry analysis for NF-kB, TGF-β1, and VEGF-A expression. Result: The NF-kB expression in the group with CaCO3 from Anadara granosa shell lower than control after 1st, 3rd and 7th days (p < 0.05). In other hand, the TGF-β1 and VEGF-A expression in the group with CaCO3 from Anadara granosa shell higher than control after 1st, 3rd and 7th days (p < 0.05). Conclusion: CaCO3 from Anadara granosa shell able to stimulate the TGF-β1 and VEGF-A and suppress the NF-kB expression in the dental pulp. This material able to develop as dentin-pulp material restoration.